Cardiotrophin‐1 Regulates Adipokine Production in 3T3‐L1 Adipocytes and Adipose Tissue From Obese Mice. Issue 9 (10th April 2017) - López‐Yoldi, Miguel; Marcos‐Gomez, Beatriz; Romero‐Lozano, María Asunción; Sáinz, Neira; Prieto, Jesús; Martínez, Jose Alfredo; Bustos, Matilde; Moreno‐Aliaga, Maria J.
Abstract : Cardiotrophin‐1 (CT‐1) belongs to the IL‐6 family of cytokines. Previous studies of our group revealed that CT‐1 is a key regulator of glucose and lipid metabolism. The aim of the present study was to analyze the in vitro and in vivo effects of CT‐1 on the production of several adipokines involved in body weight regulation, nutrient metabolism, and inflammation. For this purpose, 3T3‐L1 adipocytes were incubated with recombinant protein CT‐1 (rCT‐1) (1–40 ng/ml) for 1 and 18 h. Moreover, the acute effects of rCT‐1 administration (0.2 mg/kg, i.v.) for 30 min and 3 h on adipokines levels were also evaluated in high‐fat fed obese mice. In 3T3‐L1 adipocytes, rCT‐1 treatment downregulated the expression and secretion of leptin, resistin, and visfatin. However, rCT‐1 significantly stimulated apelin mRNA and secretion. rCT‐1 (18 h) also promoted the activation by phosphorylation of AKT, ERK 1/2, and STAT3. Interestingly, pre‐treatment with the PI3K inhibitor LY294002 reversed the stimulatory effects of rCT‐1 on apelin expression, suggesting that this pathway could be mediating the effects of rCT‐1 on apelin production. In contrast, acute administration of rCT‐1 (30 min and 3 h) to diet‐induced obese mice downregulated leptin and resistin, without significantly modifying apelin or visfatin mRNA in adipose tissue. Furthermore, CT‐1 null mice exhibited altered expression of adipokines in adipose tissue. The present study demonstrates that rCT‐1 modulates the production of adipokines in vitro and in vivo, suggesting that the regulation of the secretory function of adipocytes could be involved in the metabolic actions of this cytokine. J. Cell. Physiol. 232: 2469–2477, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The current study demonstrates that CT‐1 is capable of regulating the secretory pattern of adipokines by adipocytes, decreasing the production of pro‐inflammatory adipokines, such as leptin, resistin, and visfatin, while stimulating the secretion of apelin. These suggest that the beneficial actions of CT‐1 on glucose and lipid metabolism could be also related to its ability to control adipokine secretion and therefore the cross‐talk between adipose tissue and other key metabolic organs.